The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/ismej.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reduced pH on the microbial community of the coral Acropora eurystoma

Abstract: Rising concentrations of atmospheric carbon dioxide are acidifying the world's oceans. Surface seawater pH is 0.1 units lower than pre-industrial values and is predicted to decrease by up to 0.4 units by the end of the century. This change in pH may result in changes in the physiology of ocean organisms, in particular, organisms that build their skeletons/shells from calcium carbonate, such as corals. This physiological change may also affect other members of the coral holobiont, for example, the microbial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
205
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(226 citation statements)
references
References 56 publications
7
205
7
2
Order By: Relevance
“…Ocean acidification also affects the community structure of bacteria associated with corals. It has been reported that the relative abundance of bacteria associated with diseased and stressed corals increased under decreasing pH conditions (Meron et al, 2011). A very limited number of studies focused on the effects of ocean acidification on isolated bacterial strains have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification also affects the community structure of bacteria associated with corals. It has been reported that the relative abundance of bacteria associated with diseased and stressed corals increased under decreasing pH conditions (Meron et al, 2011). A very limited number of studies focused on the effects of ocean acidification on isolated bacterial strains have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments corals were exposed to increasing acidification, for a final pH of 7.7, for only eight weeks. Other acidification studies used lower pH values of 7.3 (Meron et al 2011) and6.7 (Vega Thurber et al 2009). In these studies, an increase in Alphaproteobacteria and decrease in Deltaproteobacteria and Bacteroidetes was detected within the SML at pH 7.3 (Meron et al 2011), and a decrease in Alphaproteobacteria and increase in Beta-, Delta-and Epsilonproteobacteria was detected at pH 6.7 (Vega Thurber et al 2009).…”
Section: Comparison Between Speciesmentioning
confidence: 99%
“…Other acidification studies used lower pH values of 7.3 (Meron et al 2011) and6.7 (Vega Thurber et al 2009). In these studies, an increase in Alphaproteobacteria and decrease in Deltaproteobacteria and Bacteroidetes was detected within the SML at pH 7.3 (Meron et al 2011), and a decrease in Alphaproteobacteria and increase in Beta-, Delta-and Epsilonproteobacteria was detected at pH 6.7 (Vega Thurber et al 2009). Although the current acidification study did not involve microbial analysis, and did not detect changes in the SML thickness, the changes in microbial populations detected in other studies suggest that the SML is affected by acidification in other ways.…”
Section: Comparison Between Speciesmentioning
confidence: 99%
See 2 more Smart Citations